(3GdJYdjbGJ hGdfhGOQs - (3GdgLQj , gGQhf Hf RcQjG GdgLQj, CHh Ydj,J (B300 (3g` s
(3ChdgG (B:s
(3MOKfG CHh jYbhH, jhSa Hf jYbhH Hf YHO GdYRjR GdcGJH , bGd (B: (3dbjJ HOhjI ef Cgd GdTGe ai HYV GdehGSe , ef Hfi eQI , aCfTOJfi dfaSgG (B: (3hcfG cef bO cGf jPcQ bHdfG ef GdfGS , ai GdMH GdPi cGf HjffG s
(3BNQgG (B:s
(3GdZGVQi , ef Cgd JQHI (B: (3hgGLQI jbjd GdPjH ajgG Yf GdZfe GdQJGY , hgh jQGgG hGdMeOddg hMOg , hUdi Gddg Ydi NjQ Ndbg , eMeO hBdg hSde JSdjeG s
(3YdHJGfs
(3GdbWYI GdChdi ai WQJgG HNWg GWdGY GdYdGeI CMeO Hf YHO GdaGOQ Hf CMeO Hf ecJhe Hf CMeO GdbjSis
(3GdfSNI GdChdis
(3HgG fXGe GdJYbjHI s
(3ChQGbgG eVWQHg GdJQJjH s
(3eYgG fSNI efbhdI efgG HNW fSN LjO ef BNQ s
Keywords: (3GddZIs